Evaluation of seed source variation and clonal propagation techniqes in Jatropha curcas linn. - Anisha Kalkoor M (Department of Tree Physiology and Forestry, College of Forestry, 2007)
A study was conducted in College of Forestry, Vellanikkara, Trichur, during the period 2005-2007 to evaluate different seed sources Jatropha curcas, a potential source of producing biodiesel for their genetic variation and to standardize efficient clonal propagation techniques. The study involved the evaluation of seed sources for their seed and seedling parameters as well as field performance of the plants. Attempts were made to standardize of macro and micro propagation techniques for the multiplication of elite genotypes.